Ответ:
Пошаговое объяснение:
f(x)=(x³/3)-x x∈[0;4]
((x³/3)-x)'=x²-1=0
(x+1)*(x-1)=0
x₁=-1 ∉ x₂=1 ∈
f(0)=(0³/3)-0=0
f(1)=(1³/3)-1=(1/3)-1=-2/3=наим.
f(4)=(4³/3)-4=(64/3)-4=21¹/₃-4=17¹/₃=наиб.
15×7=105( кг)
105-7×8=49(кг)
ответ 49 кг апеллсинов осталось продать
Р=(4см5мм+3см2мм)*2= 15см4мм=154мм
10 сантиметров.
Вроде бы так)))))
Пусть х это мальчики, у девочки.
составим уравнение.
{x+y=36
{5/8*x=0,5y
x=36-y
5/8*(36-y)=0,5y умножаем на 80
50*(36-y)=40y
1800-50y=40y
90y=1800
y=20
x=36-20=16
Ответ:мальчиков 16, девочек 20